FINANCIAL PERFORMANCE ANALYSISGOVERNMENT OF JEMBER REGENCY - Lina Ayu Candra; Muhammad Firdaus; Nanda Widaninggar (MBA - Journal of Management and Business Aplication, 2021)
This study aims to analyze the financial performance of JemberRegency Government in terms of the Regional Financial Self-Sufficiency Ratio, the Effectiveness Ratio of Local Own Revenue and Efficiency Ratio of Local Own Income and the Debt Service Coverage Ratio (DSCR) during 2014-2018. This type of research was quantitative descriptive of the Regional Government Financial Statements (LKPD) of the Jember Regency Government. The data collection techniques used were documentation, interviews, and literature study. Quantitative data analysis was used to calculate the amount of Self-SufficiencyRatio, Effectiveness and Efficiency Ratio, and Debt Service Coverage Ratio. The results showed that: (1) the Ratio of Self-Sufficiency of the Jember Regency Government as measured by Local Own Income (PAD)reached an average of 23% for each year. This condition shows that the Self-Sufficiencyofthe Jember Regency Government wasnot as expected. (2) The effectiveness ratio of PAD collection by the Government of Kabupaten Jember reaches an average of 94%. This condition indicates thatthe PAD collection has been effective. Meanwhile, the efficiency ratio of PAD collection reaches an average of 38% per year. This condition shows that the cost of collecting local revenue tends to be efficient because the efficiency ratio was less than 100%. (3) Debt Service Coverage Ratio (DSCR) in 2014 to 2018 shows that local governments were not eligible to make loans because the DSCR value was less than 2.5. Keywords:Debt Service Coverage Ratio, EffectivenessRatio, Self-SufficiencyRatio